Regulation of bacteriophage P2 late-gene expression: the ogr gene. - Christie, G E (1986)
The ogr gene product of bacteriophage P2 is a positive regulatory factor required for P2 late-gene transcription. We have determined the nucleotide sequence of the ogr gene, which encodes a basic polypeptide of 72 amino acids. P2 growth is blocked by a host mutation, rpoA109, in the alpha subunit of DNA-dependent RNA polymerase. The ogr52 mutation, which allows P2 to grow in an rpoA109 strain, was shown to be a single nucleotide change, in the codon for residue 42, that changes tyrosine to cysteine. The predicted amino acid sequence of the Ogr protein does not show similarity to DNA-binding proteins that are known to affect promoter recognition, to sigma factors, or to other characterized transcriptional regulatory proteins. We have inserted the ogr gene into a plasmid under control of the leftward promoter and operator of bacteriophage lambda. Thermal induction of ogr gene expression in this plasmid results in overproduction of a small protein that has been shown by complementation to possess Ogr function.